1977
DOI: 10.1203/00006450-197704000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Fasting Plasma Levels of Glucose, Acetoacetate, D-β-Hydroxybutyrate, Glycerol, and Lactate in the Baboon Infant: Correlation with Cerebral Uptake of Substrates and Oxygen

Abstract: Summarydata obtained in the stressed low birth weight human neonate.The energy-rich substrates available to the fasting stressed baboon neonate ~n d infant are quantitatively similar to the metabolic fuels presented to the stressed low birth weight human newborn. Within a few hours after birth, fasting arterial plasma glucose levels in the baboon neonate approximate those of 4-6-week-old baboon infants after a 20-hr fast. Lactate levels are high and comparable for both age groups. In contrast, /3-hydroxybotymt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1

Year Published

1982
1982
2001
2001

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 27 publications
1
38
1
Order By: Relevance
“…Measurements of the cerebral consumption of oxygen, glucose, and lactate have been performed in vivo in fetal sheep (26), infant baboons (27), and newborn piglets (28). The cerebral blood flow and rates of consumption of oxygen and glucose in newborn piglets have been previously demonstrated to be similar to those of human infants (13,28).…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of the cerebral consumption of oxygen, glucose, and lactate have been performed in vivo in fetal sheep (26), infant baboons (27), and newborn piglets (28). The cerebral blood flow and rates of consumption of oxygen and glucose in newborn piglets have been previously demonstrated to be similar to those of human infants (13,28).…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral energy metabolism in fasting-stressed neonatal and infant baboons was studied by Levitsky et al (1977). In the newborn animals, the mean plasma glucose concentration was 2.9 mM, and uptake of glucose by brain accounted for only 50% or less of the cerebral oxygen consumption.…”
Section: Baboonsmentioning
confidence: 99%
“…Lactate may function as cerebral cortical fuel in many newborn species, including man (14)(15)(16). Other studies among newborn beagles by our group (1 8) and Gregoire et al (17) have demonstrated release of lactate from the brain.…”
Section: Discussionmentioning
confidence: 90%
“…Both fuels pobably have little effect on cerebral energy metabolism. Glycerol in particular has not been demonstrated to be taken up by the newborn brain in mice, subhuman primates, or man (3,16,24).…”
Section: Discussionmentioning
confidence: 99%